CANDLE SYNDROME: Orofacial manifestations and dental implications. Issue 1 (December 2015) - Roberts, T.; Stephen, L.; Scott, C.; di Pasquale, T.; Naser-eldin, A.; Chetty, M.; Shaik, S.; Lewandowski, L.; Beighton, P.
Abstract A South African girl with CANDLE Syndrome is reported with emphasis on the orodental features and dental management. Clinical manifestations included short stature, wasting of the soft tissue of the arms and legs, erythematous skin eruptions and a prominent abdomen due to hepatosplenomegaly. Generalized microdontia, confirmed by tooth measurement and osteopenia of her jaws, confirmed by digitalized radiography, were previously undescribed syndromic components. Intellectual impairment posed problems during dental intervention. The carious dental lesions and poor oral hygiene were treated conservatively under local anaesthetic. Prophylactic antibiotics were administered an hour before all procedures. Due to the nature of her general condition, invasive dental procedures were minimal. Regular follow-ups were scheduled at six monthly intervals. During this period, her overall oral health status had improved markedly. The CANDLE syndrome is a rare condition with grave complications including immunosuppression and diabetes mellitus. As with many genetic disorders, the dental manifestations are often overshadowed by other more conspicuous and complex syndromic features. Recognition of both the clinical and oral changes that occur in the CANDLE syndrome facilitates accurate diagnosis and appropriate dental management of this potentially lethal condition.